Fulfilling outpatient medicine responsibilities during internal medicine residency: a quantitative study of housestaff participation with between visit tasks. Issue 1 (December 2016) - Hom, Jason; Richman, Ilana; Chen, Jonathan; Singh, Baldeep; Crump, Casey; Chi, Jeffrey
Abstract Background Internal Medicine residents experience conflict between inpatient and outpatient medicine responsibilities. Outpatient "between visit" responsibilities such as reviewing lab and imaging data, responding to medication refill requests and replying to patient inquiries compete for time and attention with inpatient duties. By examining Electronic Health Record (EHR) audits, our study quantitatively describes this balance between competing responsibilities, focusing on housestaff participation with "between visit" outpatient responsibilities. Methods We examined EHR log-in data from 2012–2013 for 41 residents (R1 to R3) assigned to a large academic center's continuity clinic. From the EHR log-in data, we examined housestaff compliance with "between visit" tasks, based on official clinic standards. We used generalized estimating equations to evaluate housestaff compliance with between visit tasks and amount of time spent on tasks. We examined the relationship between compliance with between visit tasks and resident year of training, rotation type (elective or required) and interest in primary care. Results Housestaff compliance with logging in to complete "between visit" tasks varied significantly depending on rotation, with overall compliance of 45 % during core inpatient rotations compared to 68 % during electives (p = 0.01). Compliance did not significantly vary by interest in primary care or training level. Once logged in, housestaff spent a mean 53 min per week logged in while on electives, compared to 55 min on required rotations (p = 0.90). Conclusions Our study quantitatively highlights the difficulty of attending to outpatient responsibilities during busy core inpatient rotations, which comprise the bulk of residency at our institution and at others. Our results reinforce the need to continue development and study of innovative systems for coverage of "between visit" responsibilities, including shared coverage models among multiple residents and shared coverage models between residents and clinic attendings, both of which require a balance between clinic efficiency and resident ownership, autonomy and learning.